2023
DOI: 10.1002/batt.202200522
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur‐Composites Derived from Poly(acrylonitrile) and Poly(vinylacetylene) – A Comparative Study on the Role of Pyridinic and Thioamidic Nitrogen

Abstract: Sulfurized poly(acrylonitrile) (SPAN) is a prominent example of a highly cycle stable and rate capable sulfur/polymer composite, which is solely based on covalently bound sulfur. However, so far no in‐depth study on the influence of nitrogen in the carbonaceous backbone, to which sulfur in the form of thioketones and poly(sulfides) is attached, exists. Herein, we investigated the role of nitrogen by comparing sulfur/polymer composites derived from nitrogen‐containing poly(acrylonitrile) (PAN) and nitrogen‐free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 69 publications
0
7
1
Order By: Relevance
“…While we consider our model to be representative, the real variability will lead to a further smoothing of the discharge curve. It should also be noted that the cell potential vs. Li/Li + that we obtain is somewhat overestimated compared to 66 experimental data from Fig. 7.…”
Section: Discussion and Relation To The Experimentscontrasting
confidence: 82%
See 1 more Smart Citation
“…While we consider our model to be representative, the real variability will lead to a further smoothing of the discharge curve. It should also be noted that the cell potential vs. Li/Li + that we obtain is somewhat overestimated compared to 66 experimental data from Fig. 7.…”
Section: Discussion and Relation To The Experimentscontrasting
confidence: 82%
“…Since the latter accumulates a negative charge, the partially positively charged lithium of Li 2 S can provide strong interactions, as shown in our previous work. 66 Due to the limitations of our structural model, we have to attach Li 2 S to the opposite side of our molecular model than that of the sulfur chain from which Li 2 S was released. In the realistic condensed phase, we assume Li 2 S to attach to the nitrogen backbone of a different SPAN chain in close proximity to the position of its release.…”
Section: B the Discharge Mechanismmentioning
confidence: 99%
“…The PFY results in Figure provide the chemical information in the deeper CEI, with the possibility involving bulk SPAN cathode if the thickness of CEI is within the probing depth. It is reported that the nitrogen-rich, aromatic carbon backbone in the SPAN structure plays a significant role in enabling the highly reversible redox chemistry . To gain more insights into this, C and N PFY spectra were collected for understanding the change of carbon and nitrogen in the structure after electrochemical cycling.…”
mentioning
confidence: 99%
“…It is reported that the nitrogen-rich, aromatic carbon backbone in the SPAN structure plays a significant role in enabling the highly reversible redox chemistry. 29 To gain more insights into this, C and N PFY spectra were collected for understanding the change of carbon and nitrogen in the structure after electrochemical cycling. In the carbon spectra, the different shape and peak in PFY and TEY modes suggest that the carbon species distribution has depth-dependence in the CEI.…”
mentioning
confidence: 99%
“…Since the first use of S@PAN composites as cathodes for Li-S batteries, new insights into the energy storage properties of S@PAN have been emerging. [30][31][32][33] However, before revealing the correlation between its energy storage properties and electrochemical performance, there is a mystery: the S@PAN cathode suffers from a severe and irreversible capacity loss during the first discharge cycle. Many researchers have been attracted to explore the mechanism behind this issue.…”
Section: The Energy Storage Properties Of S@pan Cathode Materialsmentioning
confidence: 99%